Case Report: Relevance of an Accurate Diagnosis and Monitoring of Infective Dermatitis Associated With Human T-Lymphotropic Virus Type 1 in Childhood - Benencio, Paula (2021)
Human T-lymphotropic virus type 1 (HTLV-1) is a neglected retrovirus distributed worldwide and the ethiological agent of several pathologies, such as adult T-cell leukemia/lymphoma (ATLL), a chronic myelopathy known as HTLV-1 associated myelopathy/tropical spastic paraparesis (HAM/TSP) and infective dermatitis associated with HTLV-1 (IDH). HTLV-1 presents tropism for CD4+ T cells and induces deregulation of the cytokine profile. IDH is a severe, chronic superinfected eczema generally associated with Staphylococcus aureus and/or Streptococcus beta haemolyticus infection that responds partially to antibiotic therapy but prompt recurrence develops upon treatment withdrawal. IDH could be a risk factor for progression toward both HAM/TSP and ATLL and, similarly to other diseases associated with HTLV-1, it is sub-diagnosed particularly in non-endemic areas. Here, we present a case of IDH in a young boy living in Buenos Aires with symptoms since 2010, at the age of 5. HTLV-1 infection was suspected and confirmed in 2016. The patient exhibited chronic dermatosis with exudative eruption involving mainly the scalp, retroauricular regions, neck and abdomen. Clinical evaluations, routine laboratory tests, full blood count, and HTLV-1 diagnosis for this case are included.